Extensive closed cell marine stratocumulus downwind of Europe—A large aerosol cloud mediated radiative effect or forcing?. Issue 12 (22nd June 2015) - Goren, Tom; Rosenfeld, Daniel
Abstract Marine stratocumulus clouds (MSC) cover large areas over the oceans and possess super sensitivity of their cloud radiative effect to changes in aerosol concentrations. Aerosols can cause transitions between regimes of fully cloudy closed cells and open cells. The possible role of aerosols in cloud cover has a big impact on the amount of reflected solar radiation from the clouds, thus potentially constitutes very large aerosol indirect radiative effect, which can exceed 100 Wm−2. It is hypothesized that continentally polluted clouds remain in closed cells regime for longer time from leaving continent and hence for longer distance away from land, thus occupying larger ocean areas with full cloud cover. Attributing this to anthropogenic aerosols would imply a very large negative radiative forcing with a significant climate impact. This possibility is confirmed by analyzing a detailed case study based on geostationary and polar‐orbiting satellite observations of the microphysical and dynamical evolution of MSC. We show that large area of closed cells was formed over the northeast Atlantic Ocean downwind of Europe in a continentally polluted air mass. The closed cells undergo cleansing process that was tracked for 3.5 days that resulted with a rapid transition from closed to open cells once the clouds started drizzling heavily. The mechanism leading to the eventual breakup of the clouds due to both meteorological and aerosol considerations is elucidated. We termed this cleansing and cloud breakup process maritimization. Further study is needed to assess the climatological significance of such situations.